Effect of The CO2 Laser as Surface Treatment on The Bond Strength of Heat Cured Soft Liner to The High Impact Acrylic Denture Base Material - Aziz, Hawraa Khalid (Journal of Baghdad College of Dentistry, 2017)
ABSRTACT Background: Soft liner material is become important in dental prosthetic treatment. They are applied to the surface of the dentures to achieve more equal force distribution , reduce localized pressure and improve denture retention by engaging undercut . So the aim of the study is to evaluate the effect of different surface treatment by air-abrasion AL2O3 and laser treatment with CO2 laser on improving the shear bond strength of the denture liner to acrylic denture base material . Materials and methods: the 30 specimens of heat cured acrylic denture base material (high Impact acrylic )and heat cured soft liner (Vertex ,Nether Lands )were prepared for this study .They were designed and divided according to type of the surface treatment 10 specimens for each group and as follows :Group I without any treatment (control group ), Group II was treated with air-abrasion (AL2O3). While group III was treated with CO2 laser which has continuous pulses with wave length(10.6) micro-meter for (15) seconds . Results: The results revealed that lowest mean values in shear bond strength the specimens treated with AL2O3 (0.498 N/mm2)and control group (0.569 N/mm2)and the highest mean values for the specimens treated with CO2 laser (0.648 N/mm2) . Conclusion: within the limitation of this study ,CO2 laser surface treatment of the heat cure acrylic denture resin with soft liner material resulted in highly significantly increased in shear bond strength values than control and AL2O3 .